Recent advances in the bioanalytical applications of dried matrix spotting for the analysis of drugs and their metabolites. (October 2013) - Zimmer, Jennifer SD; Christianson, Chad D; Johnson, Casey JL; Needham, Shane R
DBS techniques for the bioanalysis of drugs and metabolites from whole blood have been demonstrated to be a useful tool in drug development. The term dried matrix spot (DMS) has been used to indicate that the DBS technique has been applied to nonblood matrices. DMS methods often employ a color-indicating process that enhances the ability to analyze these mostly transparent fluids when spotted onto collection paper. The color-indicating dye allows the analyst to visually confirm the location of the dried sample spot. Other benefits of using a color-indicating dye include improved method accuracy and precision, because the process of adding the dye allows for the concurrent addition of the IS prior to sample addition and extraction. To date, matrices that have been analyzed using DMS include cerebrospinal fluid, synovial fluid, saliva, tears, urine and plasma.